Exploring property & real estate firm’s value: An intellectual capital perspective - Sari, Ratna Purnama; Adhivina, Vidya Vitta; Rohmatun, Yanuatri; Yennisa, Yennisa; Nusron, Lulu Amalia (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Firm’s value known as an important thing to increase simultaneously for business continuity. Especially for property & real estate sector in Indonesia which contributed more to the whole of infrastructure development. This research has an aim to examine the property & real estate firm’s value based on intellectual capital perspective. The intellectual capital consists of organizational capital, structural capital and human capital which tested to know its effect on property & real estate firm value. This study uses property and real estate sector listed in Indonesia Stock Exchange from 2016-2020. The research’s sample used 109 companies selected by purposive sampling technique. To test the data, this research using multiple linear regression analysis. The results of the study concluded that only organizational capital and structural capital which have affect on property & real estate firm value, while human capital have no effect on property & real estate firm value.